Foliar magnesium enhances rice salt tolerance by improving photosynthesis and regulating ion homeostasis - Liu, Yang; Zhu, Qi; Li, Rongkai; Wei, Renyuan; Geng, Xiaoyu; Zhang, Xiang; Wei, Huanhe; Gao, Pinglei; Xu, Ke; Dai, Qigen; Chen, Yinglong (Frontiers in Plant Science, 2025)
IntroductionHow to increase crop yield in coastal saline-alkali land has become a focus and hot topic of concern for researchers.MethodsField experiments were conducted to identify whether foliar application of magnesium sulfate (MgSO4·7H2O) can enhance rice salt tolerance and improve rice yield. Treatments with four concentrations of MgSO4·7H2O (10 g L-1, 20 g L-1, 30 g L-1, and 40 g L-1) were applied during the jointing and heading stages of rice in three fields with different salt levels in Yancheng City, Jiangsu Province, China in 2022 and 2023.ResultsResults showed that the application of magnesium sulfate, even the lowest concentration of MgSO4, could significantly increase the rice yield and total biomass under all the three salt treatments, while the increase displayed more obvious under higher salt treatment. Magnesium sulfate treatment enhanced the Rubisco enzyme activity and total chlorophyll content in rice flag leaves, delayed leaf tip wilt, and thus improved the photosynthetic capacity of rice. Additionally, magnesium sulfate treatment significantly reduced the accumulation of toxic sodium ions (Na+) in rice compared to the untreated control, accompanied with notable enhancement of Mg/Na, K/Na, P/Na, and Ca/Na.DiscussionThis study found that magnesium sulfate could enhance the salt tolerance of rice in coastal saline-alkali soils, whereas the effects vary significantly among different concentrations. Under 20 g L-¹ of MgSO4 treatment, rice leaves exhibited the highest net photosynthetic rate and total chlorophyll content, while the incidence of leaf tip wilt and the accumulation of toxic sodium ions (Na+) were minimized, resulting in the highest yield and total biomass. Therefore, 20 g L-¹ of MgSO4 is likely to be recommended as the optimal application concentration in saline-alkali areas.